How can we halve food waste by 2030 in a consumerist world? The crucial role of civil society in keeping the public attention on the green agenda - Nicolae-Ioana, Nicoleta (Civil Szemle, 2024)
The United Nations’ target for halving Food Waste (FW) and the related actions required by the 2030 Agenda should be achieved in just six years, and there is a lot to be done. Considering that FW worldwide is causing 8% to 10% of GHG, the phenomenon has become a preoccupation for the European Union (EU). As a member state, Romania is aligned with the EU policy lines regarding environment and sustainable development. Bearing in mind the consumption-based economic model, the governmental approaches, and challenges regarding environmental and sustainable development issues, a robust civil society is needed to influence the adoption of efficacious and improved public policies regarding FW and to contribute to maintaining green topics on the public agenda. This paper aims to identify the factors that explain civil society's ability to influence public policies on FW and keep these green topics on the governmental agenda. In this sense, I have carried out a literature review to identify the current situation and the levers available to Romanian civil society and data analysis. Data was gathered via 11 semi-structured in-depth interviews with representatives of central public authorities, HoReCa, civil society, and Romanian consumers conducted in the spring of 2022 for my dissertation paper. The interviews revealed that civil society as a soft power can influence Romanian public policies regarding FW and has a crucial role in covering the critical areas of education, communication, awareness, and changing consumer behavior. Moreover, the data underlines that, second to the central authorities, civil society is the next stakeholder responsible for taking action to reduce FW. The development and evolution of a solid and vigilant civil society is essential for influencing the adoption of effective and improved public policies regarding FW and contributes to maintaining green topics on the public agenda to achieve the ambitious goals set by the international community, which aim at the well-being of people, and the Planet, but also of the future generations.